Playing at the border : a story of Yo-Yo Ma - Ho, Joanna (Harper, an imprint of HarperCollinsPublishers, 2021)
". . . tell[s] an inspiring story of Yo-Yo Ma, who challenges conventions, expectations, and beliefs in order to build bridges to unite communities, people, and cultures"--Provided by publisher.